Kajian Arsitektur Simbolik Pada Bangunan Masjid - Muhammad Azka Rifqi Azza; Anisa Anisa (Arsitektur UMJ, 2019)
ABSTRACT. In architectural works, symbols become meaningful and characterize past artistic tendencies. This symbolism was not born by chance or just appeared without meaning. Symbolism in architecture sends past messages produced in certain social spaces so that they are conveyed to today's readers, so that there is an exchange of meanings that occur behind hidden symbols. Including religious symbols that indicate a link between Islamic understanding of someone with an architectural artistic tendency which later gave birth to what is called Islamic or Islamic architecture.key words: Architecture, Symbolic, Meaning.